BIAYA KEAGENAN DAN KEBIJAKAN DEVIDEN: IMPLIKASI AFILIASI GRUP BISNIS - Purdwiastuti, Maria Magdalena; Nofiyanti, Rina (Universitas Gunadarma, 2012)
This paper investigates the agency theory of dividend policy in emerging marketsuch in Indonesia. The main innovation is achieved by introducing business groupaffiliation into the original cost minimisation model. Using pooled cross sectiontime series of 59 companies listed on the Indonesian Stock Exchange with 135observasions, the result shows that only financial leverage, growth, size, and thepercentage held by the institusional that statistically significant effect the dividendpayout ratio.